Is Cooperative Learning Appropriate Instructional Methodology to Support the Implementation of Curriculum 2013 in Indonesia?: Theoretical and Cultural Analysis - Yanuar Dwi Prastyo (Bandar Lampung University (UBL), 2014)
Cooperative Learning (CL) is one of the instructional methodologies which have gain international attention in the globalization era. Cooperative learning is now utilized in schools and universities throughout most of the world in every subject area and from preschool through graduate school and adult training program (Johnson & Johnson, 2009). In hundreds of studies, cooperative learning has been associated with gains in such variables as achievement, motivation, social skills, intergroup relation, and attitudes toward school, self, and others(Dornyei, 1997; Johnson, Johnson, & Smith, 1998; Johnson, Johnson, & Stanne, 2000; Slavin, 1996). Recently,some techniques of cooperative learning have been adopted by a number of teachers in Indonesia. At the same time, the Government of Indonesia through The Ministry of Education and Culture (MOEC) introduced new curriculum, called curriculum 2013, in order to improve their education quality. As the main objectives of Curriculum 2013 are to improve students’ attitudes, skills, and knowledge (Republik Indonesia, 2012), there will be a need to be changes in the approaches to learning and teaching to be more learner-centred. This has implications for the needs of teacher training and development programs as well as instructional methodology appropriate to support the curriculum 2013.There is a requirement to provide more active learning in the classroom. This paper as part of larger study part of the Structured PhD in TESOL program University of Limerick, Ireland, is aimed at exploring if cooperative learning, which intends to include and engage learners and therefore promote active learning, is appropriate instructional methodology to support the implementation of Curriculum 2013. This paper argues that cooperative learning is an effective instructional methodology to support, and therefore achieve, three main objectives of Curriculum 2013.